ANALISIS KEMAMPUAN SISWA DALAM MENYELESAIKAN SOAL POLA BILANGAN TIPE HOTS (HIGHER ORDER THINKING SKILL) BERDASARKAN KEMAMPUAN MATEMATIKA KELAS VIII B SMP IT (ISLAM TERPADU) QURRATA A’YUN PALU - Yuyun; Awuy, Evie; Hasbi, Muh. (Jurnal Elektronik Pendidikan Matematika Tadulako, 2023)
This study aims to obtain a description of students' abilities in solving HOTS (Higher Order Thinking Skill) Type Number Pattern Problems Based on the Mathematics Ability of Class VIII B SMP IT (Integrated Islam) Qurrata A'yun Palu. This research is descriptive with a qualitative approach based on the problem-solving steps put forward by Polya. The results showed that subjects with high-level thinking skills and moderate-level thinking skills in solving mathematical problems with number patterns were as follows: (1) in understanding the problem, students with high-order thinking skills and moderate-level thinking skills demonstrated an understanding that was relevant to gathering information. The information contained in the problem can identify the problem of the problem with knowledge of the sentence "statement". (2) in planning problem solving, high-level ability subjects can plan a good strategy to achieve the goals in a problem and can choose relevant information from the problem. Meanwhile, subjects with moderate ability are quite good at planning problem solving however formulating a strategy is still not appropriate to be able to solve the problem properly. (3) in carrying out a problem-solving plan, subjects with high levels of ability are very good at executing, and carrying out planning and are able to organize and integrate problems with relevant prior knowledge, as well as subjects with moderate levels of ability (4) in re-examining, high subjects re-examining because it can monitor, check or detect the final results and unexpected events. Meanwhile, subjects with moderate ability did not re-examine because they felt unsure about solving the problems they were doing.   Keywords: ability analysis, HOTs type questions, learning outcomes, response quality, number patterns